Characteristics and outcomes of adults with chronic obstructive pulmonary disease and atrial fibrillation. Issue 22 (6th June 2018) - Durheim, Michael T; Holmes, DaJuanicia N; Blanco, Rosalia G; Allen, Larry A; Chan, Paul S; Freeman, James V; Fonarow, Gregg C; Go, Alan S; Hylek, Elaine M; Mahaffey, Kenneth W; Pokorney, Sean D; Reiffel, James A; et al.
Abstract : Objective: Chronic obstructive pulmonary disease (COPD) is associated with the development of atrial fibrillation (AF), and may complicate treatment of AF. We examined the association between COPD and symptoms, quality of life (QoL), treatment and outcomes among patients with AF. Methods: We compared patients with and without a diagnosis of COPD in the Outcomes Registry for Better Informed Treatment of Atrial Fibrillation, a prospective registry that enrolled outpatients with AF not secondary to reversible causes, from both academic and community settings. Results: Among 9749 patients with AF, 1605 (16%) had COPD. Relative to patients without COPD, those with COPD were more likely to be older, current/former smokers (73% vs 43%), have heart failure (54% vs 29%) and coronary artery disease (49% vs 34%). Oral anticoagulant and beta blocker use were similar, whereas digoxin use was more common among patients with COPD. Symptom burden was generally higher, and QoL worse, among patients with COPD (median Atrial Fibrillation Effect on QualiTy-of-Life score 76 vs 83). Patients with COPD had higher risk of all-cause mortality (adjusted HR 1.52 (95% CI 1.32 to 1.74)), cardiovascular mortality (adjusted HR 1.51 (95% CI 1.24 to 1.84)) and cardiovascular hospitalisation (adjusted HR 1.15 (95% CI 1.05 to 1.26)). Patients with COPD also had higher risk of major bleeding events (adjusted HR 1.25 (95% CI 1.05 to 1.50)). There did not appear to be associations between COPD and AF progression, ischaemic events or new-onset heart failure. Conclusions: Among patients with AF, COPD is associated with higher symptom burden, worse QoL, and worse cardiovascular and bleeding outcomes. These associations were not fully explained by cardiovascular risk factors, AF treatment or smoking history. Clinical registration number: NCT01165710